Analisa Dampak Kemitraan Contract Farming Terhadap Pendapatan Petani Ubi Kayu (Studi Kasus) di Desa Sampecita Kecamatan Kutalimbaru Kabupaten Deli Serdang - Sajar, Suryani Yani; Setiawan, Andi; Sitepu, Sri Mahreni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cassava is one of the food crops widely cultivated by farmers in Glugur Rimbun, Sampecita Village. This plant is a secondary crop with the largest harvest area in Kutalimbaru District. Partnerships between farmers and suppliers are certainly a breakthrough in developing farming businesses. This is because in addition to the uncertainty of marketing and prices, farmers will also be able to adopt the science and technology set by the supplier in an effort to increase production and quality. This study aims to analyze the partnership pattern of farmers with cassava processing companies, the influence of production factors (seedling area, labor and fertilizer) and farmer income analysis, to determine the feasibility of farming businesses. The partnership pattern carried out between farmers/landowners and UD. Kreasi Lutvi is structured in a cooperation contract, where the partner UD. Kreasi Lutvi is responsible for cultivating cassava, providing production facilities ranging from seeds, herbicides, fertilizers, agricultural tools and labor and buying cassava harvests at an agreed price. Farmers provide land and supervisors in cassava cultivation activities until harvest. The feasibility analysis of cassava business is as follows: production costs incurred per ha of Rp 14,500,000.00,- the amount of cassava production per ha is 23,405 kg, the selling price is Rp. 1,450 / kg, the total income is Rp33,937,250/ha and the income is Rp19,437,250.00/ha The R/C value is 2.34, the BEP unit value is 10,000/kg and the BEP price is Rp619.5/kg. This shows that the cassava business in the Glugur Rimbun land is feasible to be run.